1999
DOI: 10.1177/0310057x9902700206
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Central Venous Catheter Related Infection in Intensive Care Patients

Abstract: This study investigated the incidence of and risk factors for central venous catheter (CVC) infection in intensive care. CVCs were prospectively studied in patients who had lines inserted in general or neurosurgical intensive care and were expected to have the line in situ for at least 72 hours. Catheters (n=119) were cultured for CVC-related infection (CRI; >15 colony forming units) and blood cultures done when indicated. CRI was identified in 32 (26.9%) catheters, CVC related bacteraemia in five cases (4.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 25 publications
1
31
0
3
Order By: Relevance
“…This is consistent with other recent reports. 14,19,22,23 More important perhaps was strict adherence to infection control procedures by participating clinicians. A recent review concluded that these methods are essential when using intravascular catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other recent reports. 14,19,22,23 More important perhaps was strict adherence to infection control procedures by participating clinicians. A recent review concluded that these methods are essential when using intravascular catheters.…”
Section: Discussionmentioning
confidence: 99%
“…This definition for bacteraemia has recently been used by other investigators. 1,[18][19][20] Cultures and antimicrobial susceptibility Following catheter removal, the distal tip and a 3-mm intracutaneous segment were aseptically cut from the catheter and placed in individual containers for microbial evaluation. A core laboratory (Esoterix, Inc., San Antonio, TX, USA) was used to ensure consistency when performing and evaluating roll-plate, sonication and blood cultures.…”
Section: Definitionsmentioning
confidence: 99%
“…Potential acute complications of catheter-related thrombosis include increase in the risk of sepsis, life-threatening superior vena cava syndrome, 380 Y. Finkelstein et al and pulmonary embolism [3,5]. The frequency of those complications as well as the optimal therapy in children with symptomatic and asymptomatic thrombosis of the upper venous system thrombosis is currently unknown and awaits future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with thalassemia major (TM) with severe secondary iron overload, long-term chelation therapy with deferoxamine via a CVL avoids the pain associated with subcutaneous administration, allows for higher doses, and can extend survival and diminish cardiac arrhythmias and failure [1,2]. However, the use of CVLs is being reevaluated owing to their high rate of complications, such as infection and thrombosis [3][4][5]. Some authors have suggested that the majority of venous thromboembolic events in infants and young children with CVLs are associated with the presence of genetic risk factors for thrombophilia [6].…”
Section: Y Finkelstein Et Almentioning
confidence: 99%
“…Several methods have been proposed to prevent infectious complications. Selection of the subclavian site appears to minimize the risk of infectious complications [6,8,9]. Antimicrobialimpregnated catheters and/or catheter hubs were reported to reduce the risks and costs [1,6].…”
Section: Discussionmentioning
confidence: 99%